Combined Sabal and Urtica Extracts (WS® 1541) Exert Anti-proliferative and Anti-inflammatory Effects in a Mouse Model of Benign Prostate Hyperplasia - Pigat, Natascha; Reyes-Gomez, Edouard; Boutillon, Florence; Palea, Stefano; Barry Delongchamps, Nicolas; Koch, Egon; Goffin, Vincent (Frontiers in Pharmacology, 2019)
WS® 1541 is a phytopharmaceutical drug combination containing a lipophilic extract from fruits of Sabal serrulata (WS® 1473) and an aqueous ethanolic extract from roots of Urtica dioica (WS® 1031). It is approved in several countries worldwide for the treatment of lower urinary tract syndrome (LUTS) linked to benign prostate hyperplasia (BPH). Clinical studies have demonstrated the efficacy of this unique combination in the treatment of BPH-related LUTS. However, its mechanisms of action in vivo remain partly uncharacterized. The aim of this study was to take advantage of a validated mouse model of BPH to better characterize its growth-inhibitory and anti-inflammatory properties. We used the probasin-prolactin (Pb-PRL) transgenic mouse model in which prostate-specific overexpression of prolactin results in several features of the human disease including tissue hypertrophy, epithelial hyperplasia, increased stromal cellularity, inflammation, and LUTS. Six month-old heterozygous Pb-PRL male mice were randomly distributed to five groups (11-12 animals/group) orally treated for 28 consecutive days with WS® 1541 (300, 600 or 900 mg/kg/day), the 5alpha-reductase inhibitor finasteride used as reference (5 mg/kg/day), or vehicle (olive oil 5 ml/kg/day). Administration of WS® 1541 was well tolerated and caused a dose-dependent reduction of prostate weight (vs vehicle) that was statistically significant at the two highest doses. This effect was accompanied by a reduction in prostate cell proliferation as assessed by lower Ki-67 expression (qPCR and immunohistochemistry). In contrast, finasteride had no or only a mild effect on these parameters. The growth-inhibitory activity of WS® 1541 was accompanied by a strong anti-inflammatory effect as evidenced by the reduced infiltration of cells expressing the leukocyte common antigen CD45. In sharp contrast, finasteride significantly increased the prostate inflammatory status according to this readout. Molecular profiling (qPCR) of 23 selected pro-inflammatory genes confirmed the strong anti-inflammatory potency of WS® 1541 compared to finasteride. Since treatment of WS® 1541 did not interfere with transgene expression and activity in the prostate of Pb-PRL mice, the effects observed in this study are entirely attributable to the intrinsic pharmacological action of the drug combination.